Study of the association between genotypic potential and linoleic acid tolerance with microbial production of conjugated linoleic acid - Fontes, Ana Luiza (2023)
Probiotic bacteria have been shown to produce the bioactive conjugated linoleic acid (CLA) from linoleic acid (LA), this being associated with a detoxifying mechanism. Primers employed in genotypic selection are generally species-specific. Therefore, this work aimed to identify CLA producers by previously screening genes encoding enzymes involved in LA isomerization with primers designed based on conserved motifs among different species. Moreover, it was intended to evaluate the relation of LA tolerance with CLA production potential. Genotypically positive strains were further cultured with LA and CLA quantified. At least one of the screened genes was detected in 39 out of 85 strains, where designed primers allowed the identification of more potential producers than reported ones. The LA tolerance (<1-5 mg/mL) was shown to be independent of genotypical positivity/negativity. Only four strains exhibited CLA production (4.94-312.39 μg/mL). Thus, primers targeting conserved motifs are more efficient in the selection of potential CLA producers, however, this identification cannot rely solely on genotypic screening and LA tolerance.